HUBUNGAN POSISI DAN LAMA DUDUK DENGAN NYERI PUNGGUNG BAWAH (NPB) MEKANIK KRONIK PADA KARYAWAN BANK - Pirade, Aron; Angliadi, Engeline; Sengkey, Lidwina S. (JURNAL BIOMEDIK : JBM, 2013)
Abstract: Low Back Pain (LBP) is the most frequent musculosceletal issue found in daily work. Extenuating physical positions comprise 80-85% of the caues of LBP. In the medical world, a lot of causes of LBP do not identify the pathoanatomical disorders. These factors are e.g.: body in static position while working and the working body position leaning heavily on the vertebra (for example: sitting in a hunched position, sitting upright without back support, or working for unsually long periods of time). Until now in Manado no study has been carried out to show the correlation between LBP and the sitting position, or the duration of work. This study aimed to find out the correlation between chronic LBP and the sitting position or the duration of work among bank employees in one of the goverment banks in Manado. The results showed that there were 69 respondents involved in this study. Chronic LBP was found in 62 respondents (90%). Up stright position while sitting was the most frequent position that caused chronic LBP in 28 respondents. The average time used for working with sitting position was 7-8 hours which caused chronic LBP among 31 respondents of the group with the work time from 11.00-13.59. A P-value of 0.000 (<0.05) showed that there was a strong correlation between sitting position and chronic LBP. Duration of work also showed a strong correlation with chronic LBP with a P-value of 0.000. Conclusion: There were strong correlations beween chronic low back pain with sitting position while working and duration of work. Keywords: chronic LBP chronic, sitting position, duration of work, bank employees. Abstrak:Nyeri Punggung Bawah (NPB) merupakan gangguan muskuloskeletal yang paling sering dijumpai dalam aktivitas kerja. Faktor mekanik mencakup 80-85% dari keseluruhan penyebaNPB. Patoanatomi sering tidak dapat memberikan ketepatan diagnosis NPB oleh proses mekanik. Faktor mekanik yang mempercepat terjadinya gangguan NPB antara lain posisi badan yang cenderung statis, posisi badan yang cenderung memperberat kerja tulang-tulang vertebra seperti posisi badan membungkuk, tegak tanpa sandaran, dan waktu bekerja yang lama saat duduk. Hubungan NPB dengan posisi dan lama duduk belum pernah dilaporkan di Kota Manado. Penelitian ini bertujuan untuk mengetahui hubungan posisi dan lama duduk saat bekerja yang dapat menimbulkan NPB mekanik kronik pada karyawan bank. Hasil penelitian memperlihatkan dari keseluruhan responden yang berjumlah 69 orang, didapatkan 62 responden (90%) yang mengalami NPB mekanik kronik. Posisi duduk tegak tanpa sandaran merupakan posisi terbanyak menimbulkan NPB mekanik kronik pada 28 responden. Rata-rata lama duduk bekerja 7-8 jam menyebabkan NPB pada kelompok pukul 11.00-13.59 sebanyak 31 responden. Analisis statistik menggunakan uji chi-square memperlihatkan adanya korelasi yang kuat (P = 0,000) antara posisi duduk dan NBP mekanik kronik Lama duduk juga berkorelasi kuat dengan NBP mekanik kronik (P = 0,000). Simpulan: Terdapat hubungan yang kuat antara NBP mekanik kronik dengan posisi dan lama duduk pada karyawan bank. Kata kunci: NPB mekanik kronik, posisi duduk, lama duduk, karyawan bank.